When the going gets rough – studying the effect of surface roughness on the adhesive abilities of tree frogs - Crawford, Niall; Endlein, Thomas; Pham, Jonathan T.; Riehle, Mathis; Barnes, W. Jon P. (Beilstein Journal of Nanotechnology, 2016)
Tree frogs need to adhere to surfaces of various roughnesses in their natural habitats; these include bark, leaves and rocks. Rough surfaces can alter the effectiveness of their toe pads, due to factors such as a change of real contact area and abrasion of the pad epithelium. Here, we tested the effect of surface roughness on the attachment abilities of the tree frog Litoria caerulea. This was done by testing shear and adhesive forces on artificial surfaces with controlled roughness, both on single toe pads and whole animal scales. It was shown that frogs can stick 2–3 times better on small scale roughnesses (3–6 µm asperities), producing higher adhesive and frictional forces, but relatively poorly on the larger scale roughnesses tested (58.5–562.5 µm asperities). Our experiments suggested that, on such surfaces, the pads secrete insufficient fluid to fill the space under the pad, leaving air pockets that would significantly reduce the Laplace pressure component of capillarity. Therefore, we measured how well the adhesive toe pad would conform to spherical asperities of known sizes using interference reflection microscopy. Based on experiments where the conformation of the pad to individual asperities was examined microscopically, our calculations indicate that the pad epithelium has a low elastic modulus, making it highly deformable.
Keywords: adhesion; friction; Litoria caerulea; roughness; tree frog

The biomechanics of tree frog adhesion under challenging conditions - Crawford, N. A. (University of Glasgow, 2016)

(untitled) - Hanna, G.; Barnes, W. J. P. (J. Exp. Biol., 1991)

(untitled) - Federle, W.; Barnes, W. J. P.; Baumgartner, W.; Drechsler, P.; Smith, J. M. (J. R. Soc., Interface, 2006)

(untitled) - Barthlott, W.; Neinhuis, C. (Planta, 1997)

(untitled) - Koch, K.; Bhushan, B.; Barthlott, W. (Soft Matter, 2008)

Introduction to Tribology - Bhushan, B. (Jon Wiley & Sons, Inc., 2002)

Biological Micro- and nanotribology: Nature’s Solutions - Scherge, M.; Gorb, S. N. (Springer, 2001)

(untitled) - Endlein, T.; Barnes, W. J. P.; Samuel, D. S.; Crawford, N. A.; Biaw, A. B.; Grafe, U. (PLoS One, 2013)

(untitled) - Prüm, B.; Seidel, R.; Bohn, H. F.; Speck, T. (J. R. Soc., Interface, 2012)

(untitled) - Prüm, B.; Bohn, H. F.; Seidel, R.; Rubach, S.; Speck, T. (Acta Biomater., 2013)

Scanning electron microscopy in taxonomy and functional morphology - Barthlott, W. (Scanning electron microscopy of the epidermal surface in plants, 1990)

(untitled) - Federle, W.; Maschwitz, U.; Fiala, B.; Riederer, M.; Hölldobler, B. (Oecologia, 1997)

(untitled) - Barnes, W. J. P.; Oines, C.; Smith, J. M. (J. Comp. Physiol., A, 2006)

(untitled) - Smith, J. M.; Barnes, W. J. P.; Downie, J. R.; Ruxton, G. D. (J. Zool., 2006)

(untitled) - Barnes, W. J. P.; Smith, J. M.; Oines, C.; Mundl, M. (Tire Tech. Int., 2002)

(untitled) - Emerson, S. B.; Diehl, D. (Biol. J. Linn. Soc., 1980)

(untitled) - Zhou, Y.; Robinson, A.; Steiner, U.; Federle, W. (J. R. Soc., Interface, 2014)

(untitled) - Barnes, W. J. P.; Baum, M.; Peisker, H.; Gorb, S. N. (J. Morphol., 2013)

(untitled) - Barnes, W. J. P.; Goodwyn, P. J. P.; Nokhbatolfoghahai, M.; Gorb, S. N. (J. Comp. Physiol., A, 2011)

(untitled) - Persson, B. N. J. (J. Phys.: Condens. Matter, 2007)

(untitled) - Endlein, T.; Ji, A.; Samuel, D. A.; Yao, N.; Wang, Z.; Barnes, W. J. P.; Federle, W.; Kappl, M.; Zhengdong, D. (J. R. Soc., Interface, 2013)

Encyclopedia of nanotechnology, Part 2 - Endlein, T.; Barnes, W. J. P. (Wet adhesion in tree and torrent frogs, 2015)

(untitled) - Drotlef, D. M.; Appel, E.; Peisker, H.; Dening, K.; del Campo, A.; Gorb, S. N.; Barnes, W. J. P. (Interface Focus, 2015)

(untitled) - Kappl, M.; Kaveh, F.; Barnes, W. J. P. (Bioinspiration Biomimetics, 2016)

(untitled) - Zhu, L.-Y. (IEEE Trans. Magn., 1999)

(untitled) - Autumn, K.; Dittmore, A.; Santos, D.; Spenko, M.; Cutkosky, M. (J. Exp. Biol., 2006)

(untitled) - Gingell, D.; Todd, I. (Biophys. J., 1979)

Molecular adhesion and its applications: the sticky universe - Kendall, K. (Kluwer Academic Publishers, 2001)

(untitled) - Persson, B. N. J.; Brener, E. A. (Phys. Rev. E, 2005)

(untitled) - Matz, D.; Wuttke, S.; Barnes, W. J. P. (Comp. Biochem. Physiol., Part A: Mol. Integr. Physiol., 2008)

(untitled) - Hutt, W.; Persson, B. N. J. (J. Chem. Phys., 2016)

(untitled) - Crawford, N.; Endlein, T.; Barnes, W. J. P. (J. Exp. Biol., 2012)

(untitled) - Kendall, K. (J. Phys. D: Appl. Phys., 1975)

(untitled) - Lorenz, B.; Krick, B. A.; Mulakaluri, N.; Smolyakova, M.; Dieluweit, S.; Sawyer, W. G.; Persson, B. N. J. (J. Phys.: Condens. Matter, 2013)

(untitled) - Huber, G.; Gorb, S. N.; Hosoda, N.; Spolenak, R.; Arzt, E. (Acta Biomater., 2007)

(untitled) - Wolff, J. O.; Gorb, S. N. (J. Exp. Biol., 2012)

(untitled) - Clemente, C. J.; Dirks, J.-H.; Barbero, D.; Steiner, U.; Federle, W. (J. Comp. Physiol., A, 2009)

(untitled) - Kovalev, A. E.; Filippov, A. E.; Gorb, S. N. (J. R. Soc., Interface, 2013)

(untitled) - Zani, P. A. (J. Evol. Biol., 2000)

(untitled) - Kesel, A. B.; Martin, A.; Seidl, T. (J. Exp. Biol., 2003)

(untitled) - Dai, Z.; Gorb, S. N.; Schwarz, U. (J. Exp. Biol., 2002)

(untitled) - Bullock, J. M. R.; Federle, W. (Insect Sci., 2011)

(untitled) - Labonte, D.; Federle, W. (Philos. Trans. R. Soc., B, 2015)

(untitled) - Endlein, T.; Federle, W. (J. Comp. Physiol., A, 2008)

(untitled) - Song, Y.; Dai, Z.; Wang, Z.; Ji, A.; Gorb, S. N. (Sci. Rep., 2016)

(untitled) - Bauer, U.; Scharmann, M.; Skepper, J.; Federle, W. (Proc. R. Soc. London, Ser. B, 2013)

(untitled) - Gaume, L.; Perret, P.; Gorb, E.; Gorb, S.; Labat, J.-J.; Rowe, N. (Arthropod Struct. Dev., 2004)

(untitled) - Bijma, N. N.; Gorb, S. N.; Kleinteich, T. (J. Comp. Physiol., A, 2016)

(untitled) - Herrel, A.; Perrenoud, M.; Decamps, T.; Abdala, V.; Manzano, A.; Pouydebat, E. (J. Exp. Biol., 2013)

Encyclopedia of Nanotechnology - Lang, A.; Habegger, M. L.; Motta, P. (Shark Skin Drag Reduction, 2015)

(untitled) - Neinhuis, C.; Barthlott, W. (Ann. Bot. (Oxford, U. K.), 1997)

Encyclopedia of Nanotechnology - Kroner, E.; Arzt, E. (Gecko adhesion, 2015)

(untitled) - Chen, H.; Zhang, L.; Zhang, D.; Zhang, P.; Han, Z. (ACS Appl. Mater. Interfaces, 2015)